Optimization of Organoleptic Properties, Iron, and Protein Content in Cookies with the Addition of Sorghum Flour and Soybean Flour - Farida Wahyu Ningtyias; Sulistiyani Sulistiyani; Jeni Dian Dianata (Window of Health : Jurnal Kesehatan, 2026)
Anemia is a condition in which the level of hemoglobin (Hb) in the body is below normal, caused by a lack of intake of the iron and protein the body needs. Anemia in young women can reduce the immune system's ability and learning achievement. The World Health Organization (WHO) states that the prevalence of anemia among adolescent girls worldwide ranges from 40% to 88%, and the prevalence of anemia in developing countries reaches around 57.3%. Meanwhile, in Indonesia, according to the 2018 Indonesian Basic Health Research, the prevalence of anemia among adolescents is 32%. The purpose of this study was to analyze the effect of adding sorghum flour and soybean flour on levels of iron, protein and the acceptability of cookies as an alternative snack to prevent anemia in young women. This type of research is a quasi-experimental research design with a Posttest Only Control Group Design. Tests for iron and protein levels were carried out at the Food Analysis Laboratory of the Jember State Polytechnic while the power tests were carried out on 28 grade 8 students at SMPN 1 Kalisat Jember. This research was conducted from February to April The results showed that as the proportion of added soy flour increased and the proportion of sorghum flour decreased, the average iron and protein levels increased. The highest mean values for iron and protein were found in treatment X3 with iron levels of 4.79 mg and protein levels of 14.89 g. The most preferred taste acceptance is in treatment X1 and X2 by 50% with a very favorable rating (SS). In conclusion, the addition of sorghum flour and soybean flour to cookies had a significant effect on the levels of iron and protein in cookies but did not have a significant difference on the acceptance of taste, color and texture of cookies.